ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK (TAX AVOIDANCE) - Rizka Oktagiani; Azwir Nasir; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This aim of this research is the effect of return on asset, leverage, size and fiscal kompensation to the tax avoidance. The sample of this research 17 transportation companies whichh are listed in Indonesia Stock Exchange in the period 2010-2012. To analysis data, the research employes multiple linear regression analysis. The results of this research indicate return on asset, size of company and loss fiscal carryfoward have significant effect on tax avoidance. In contrast leverage has no significant effect on tax avoidance. while the coefficient of determination study was 0.240 %, it’s mean 24 % that’s tax avoidance effect of return on asset, leverage, size of company and loss fiscal carryfoward while 76 % effect other variabel.Keywords: Return on Asset, Leverage, Size of company and loss fiscal carryfoward